The Supply Chain Management Marketing Strategy Analysis in Increasing the Sales Volume - Rifki Akmal Tanjung; Nurbaiti Nurbaiti; Nuri Aslami (Almana : Jurnal Manajemen dan Bisnis, 2023)
Each company has a strategy that is different from the others to market its products. Marketing strategy is very important because it supports the survival of a company. Because if a company waits for an appropriate and appropriate marketing strategy, it will affect consumer buying interest in the product which is being produced. Purchase intention is increasing because of an appropriate marketing strategy. This study aims to find out how the marketing strategy used by the Kipang Sisera Panyabung Mandailing Natal factory in increasing sales volume and attracts consumer interest. The type of research used is the research method Qualitative using a field research approach (Field research) by conducting observations and interviews or interviews with factory owners and employees. And the research object is the Sisera kipang factory. Based on the analysis carried out using SWOT analysis where the Kipang Sisera Factory increases sales volume by using a product diversification strategy. Setting affordable prices, lots of promotions on certain days, maintaining familiarity with suppliers and consumers, and maintaining product quality. And it can be concluded that the marketing strategy of the Kipang Sisera factory can increase sales volume from the right marketing strategy.